1997
DOI: 10.1128/aac.41.3.672
|View full text |Cite
|
Sign up to set email alerts
|

Fungicidal action of aureobasidin A, a cyclic depsipeptide antifungal antibiotic, against Saccharomyces cerevisiae

Abstract: Aureobasidin A, an antifungal antibiotic inhibiting a wide range of pathogenic fungi, is lethal for growing cells of susceptible fungi. We did cytological studies on the mechanism of its fungicidal action against Saccharomyces cerevisiae. When cultures were treated with 5.0 micrograms of aureobasidin A per ml, the numbers of viable cells started to decrease after 2 to 3 h of incubation, and most cells had lost viability after 5 to 6 h. When cell death in the treated cultures began, amino acids released by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 23 publications
5
77
1
Order By: Relevance
“…These data suggest that nano-Ag inhibited some cellular processes which are involved in normal bud growth. Endo et al have reported that the inhibition of bud growth correlates with membrane damage (Endo et al 1997). This report suggests that nano-Ag inhibits the normal budding process, probably through the destruction of membrane integrity.…”
Section: Discussionmentioning
confidence: 88%
“…These data suggest that nano-Ag inhibited some cellular processes which are involved in normal bud growth. Endo et al have reported that the inhibition of bud growth correlates with membrane damage (Endo et al 1997). This report suggests that nano-Ag inhibits the normal budding process, probably through the destruction of membrane integrity.…”
Section: Discussionmentioning
confidence: 88%
“…However, in A. nidulans and S. cerevisiae treatment with AbA caused cell cycle arrest and inhibition of polar growth. The cell cycle arrest was associated with the accumulation of ceramides produced after the inhibition of the IPC synthase (Cheng et al, 2003;Endo et al, 1997). Then, either AbA treatment of U. maydis cells does not result in ceramide accumulation to sufficient levels to arrest cell cycle or ceramide accumulation does not cause cell cycle arrest in this organism.…”
Section: Discussionmentioning
confidence: 95%
“…In A. nidulans and S. cerevisiae inhibition of IPC synthase by treatment with AbA results in cell cycle arrest, most likely as a consequence of ceramide accumulation (Cheng et al, 2003;Endo et al, 1997). U. maydis poses a special case since it naturally arrests its cell cycle at G2 during b-dependent filamentation.…”
Section: Inhibition Of Sphingolipid Biosynthesis Affect Polar Growth mentioning
confidence: 98%
See 2 more Smart Citations